Gas-Assisted Spray Fabrication of Reticulated TiO2 Scaffolds for Perovskite Solar Applications - Sana Handor; Andrei Gabriel Tomulescu; Viorica Stancu; Abdelati Razouk; Aurelian Catalin Galca; Lucia Nicoleta Leonat (Micromachines)
This study presents a systematic approach to engineering the electron transport layer (ETL) in perovskite solar cells using a spray deposition technique to fabricate sequentially compact and mesoporous titanium dioxide (c-TiO2, m-TiO2) films. The spray coating method leads to the development of a distinct reticulated morphology characterized by well-defined wavy-like surface features and significantly increased roughness—at least twice that of spin-coated mesoporous films. The increased interfacial area between the mesoporous TiO2 and the perovskite layer facilitates more efficient charge transfer, contributing to higher device performance. By optimizing the deposition parameters, particularly the number of spray cycles for the m-TiO2 layer, we achieve a significant enhancement in device performance, with improvements in power conversion efficiency (PCE), reduced series resistance, and minimized hysteresis. Our results demonstrate that an optimal film thickness promotes better perovskite anchoring, while excessive deposition impedes light transmission and increases sheet resistance. These findings advance the practical fabrication of high-performance perovskite solar cells using simple solution-processing techniques and highlights the potential of scalable spray deposition methods for industrial-scale fabrication.